Proceedings of the Workshop on Drinfeld Modules, Modular Schemes and Applications: Alden-Biesen, 9-14 September 1996 - Gekeler, Ernst-Ulrich (World Scientific Publishing Co. Pte Ltd, 1997)
1. Introduction to Drinfeld Modules -- 2. Moduli Schemes of Drinfeld Modules -- 3. Analytic Theory of Drinfeld Modules -- 4. A Guide to Explicit Class Field Theory in Global Function Fields -- 5. Drinfeld Modules Over Finite Fields -- 6. Some Rigid Geometry -- 7. The Structure of Ω and Its Quotients Λ/Ω -- 8. Analytic Compactification and Modular Forms -- 9. Algebraic Compactification and Modular Interpretation -- 10. A Survey of Drinfeld Modular Form -- 11. Automorphic Forms and Drinfeld's Reciprocity Law -- 12. Jacquet-Langlands Theory Over K and Relations With Elliptic Curves -- Research Papers: On Hilbert Class Field Towers of Global Function Fields -- Drinfeld Modular Forms of Level T -- Explicit Reciprocity Law for a Rank One Drinfeld Fq[t]-Module -- Groups of Elliptic Units and Torsion Points of Drinfeld Modules -- L-Series of Automorphic Cusp Forms of Drinfeld Type -- Hyperelliptic Drinfeld Modular Curves -- Local Height Pairings of Heegner Points on Drinfeld Curves.
Includes bibliographical references